2001
DOI: 10.1177/1532673x01029002003
|View full text |Cite
|
Sign up to set email alerts
|

Absentee Voting, Mobilization, and Participation

Abstract: Liberal absentee laws are designed to make voting easier, which should stimulate turnout. Using data from the National Election Studies, we test the hypothesis that persons who choose to vote early are already highly motivated to participate in the political process. We find support for this hypothesis, which raises questions about the extent to which liberal absentee laws can expand the electorate. Furthermore, contrary to past research, we see the Republican advantage in absentee voting as a result of self-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 12 publications
(17 reference statements)
2
51
0
Order By: Relevance
“…Specifically, early voters tend to be strong partisans, strong ideologues, and more interested in politics. These findings are corroborated by Berinsky, Burns, and Traugott (2001) and Karp and Banducci (2001).…”
Section: What We Know About Early Votingsupporting
confidence: 63%
See 1 more Smart Citation
“…Specifically, early voters tend to be strong partisans, strong ideologues, and more interested in politics. These findings are corroborated by Berinsky, Burns, and Traugott (2001) and Karp and Banducci (2001).…”
Section: What We Know About Early Votingsupporting
confidence: 63%
“…However, he did find that when liberalized absentee voting requirements are combined with efforts by political parties to encourage the use of absentee ballots, overall turnout does increase. Karp and Banducci (2001) had similar findings; the authors showed that liberal absentee laws do not expand the overall electorate; they just allow those already likely to vote to do so by mail.…”
Section: What We Know About Early Votingmentioning
confidence: 77%
“…Neely and Richardson concluded that early voting simply allows those who would have voted on Election Day to vote at a more convenient time. Karp and Banducci (2001) investigated whether liberal absentee voting laws expand the electorate using a national sample (42 states) of National Election Study data pooled from five successive elections. The authors found that older, more educated, politically active voters are more likely to vote absentee than other voters.…”
Section: Early Votingmentioning
confidence: 99%
“…(p. 502) Regardless of whether the decline in turnout is real or artifactually induced by using the VAP denominator, concerns over low voter turnout have prompted a series of reforms. Efforts to increase voter turnout include the National Voter Registration Act (Martinez & Hill, 1999) and the passage of liberal absentee-voting laws in several states (Karp & Banducci, 2001). Lawmakers and citizen groups have been looking to the Internet as a possible way to increase electoral participation.…”
Section: Voting Reformsmentioning
confidence: 99%